INDOOR AIR QUALITY ASSESSMENT DURING LOCKDOWNS AND IMPROVEMENT STRATEGIES FOR THE RESIDENTIAL HOUSES IN RURAL AREAS IN KAZAKHSTAN - Otesh, Nurlan (Nazarbayev University School of Engineering and Digital Sciences, 2021)
It is well known that people spend most of their time indoors, hence Indoor Environmental Quality is vital and the first thing we need to put our focus on. The evaluation of indoor environment quality concerns both, how well the environment was built and the well-being of the building's occupants. The reason behind this concern is that majority of outdoor and indoor sources and equipment such as cooking and heating systems, can lead to poor IAQ and high concentrations of indoor pollutants.
Keywords: type of access: open access; lockdown; rural area; Indoor air quality assessment; residential houses